2016
DOI: 10.1177/0269758016650355
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of local commissioning on victim services in England and Wales

Abstract: This article looks at the shift that has taken place in the funding of victim services in England and Wales, following the decision to appoint Police and Crime Commissioners, and give them the responsibility to commission such services at the local level. Over the past 40 years or so the voluntary sector agency Victim Support was 'the major victims' agency' to which the majority of victims who reported crime to the police were referred. Victim Support therefore enjoyed reliable and consistent funding from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 22 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…Both Simmonds (2016) and Mawby (2016) argue that the reality for the local commissioning framework for smaller agencies is that they are now bidding for more complex contracts, which they do not always have the infrastructure to support, and that making competitive bids is itself a time consuming and expensive process that requires considerable expertise. A review of the progression of this commissioning scheme so far has supported these claims.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both Simmonds (2016) and Mawby (2016) argue that the reality for the local commissioning framework for smaller agencies is that they are now bidding for more complex contracts, which they do not always have the infrastructure to support, and that making competitive bids is itself a time consuming and expensive process that requires considerable expertise. A review of the progression of this commissioning scheme so far has supported these claims.…”
Section: Discussionmentioning
confidence: 99%
“…Reaffirmation of the myth that only a small proportion of victims need support may lead to the disenfranchisement of most victims. (p.217) Indeed, on this point Simmonds (2016) has discussed the irony that the localised service provisions model as a whole is much more in keeping with Victim Support's prior status as a federation of individual organisations rather than as a national charity, the Labour government having convinced the organisation to adopt that status in 2008.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Swedish women's shelters, once a grassroots feminist movement, currently carry out commissioned work for the municipal social services on a contract basis (Enander et al, 2013). Studies in other countries, such as the United Kingdom (Simmonds, 2016), have also shown a shift in the funding of generic victim services, from reliable and consistent state funding to local commissioning where 'the market' is seen as the best way to achieve efficient and cost-effective services.…”
Section: Introductionmentioning
confidence: 99%